1989
DOI: 10.18174/njas.v37i2.16644
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the response of sugar beet and potatoes to fertilizer nitrogen and soil mineral nitrogen.

Abstract: A statistical analysis was performed to investigate if, and to what extent, the response of sugarbeet and potatoes to fertilizer N depended on the amount of mineral N already present in the soil, soil type, and prior application of organic manures. For this purpose the results of 150 field trials with sugarbeet and 98 with potatoes were used. The analysis was focussed on the within-block stratum of variation in yield, where regression models were fitted to describe the response to N. For both sugarbeet and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
(10 reference statements)
1
12
0
1
Order By: Relevance
“…2). These percentages are similar to those observed by Neeteson & Zwetsloot (1989), who concluded that, during spring and early summer, soil within the 60-100 cm horizon contributed little mineral N to the crop. However, Brown & Dunham (1986) showed that the soil is exploited by the fibrous root system of sugarbeet to a depth of 60 cm within c. 70 days of sowing, and deeper within the following few weeks.…”
Section: Relationships Between N Mtn N Mineralized and N Fertilizersupporting
confidence: 90%
See 1 more Smart Citation
“…2). These percentages are similar to those observed by Neeteson & Zwetsloot (1989), who concluded that, during spring and early summer, soil within the 60-100 cm horizon contributed little mineral N to the crop. However, Brown & Dunham (1986) showed that the soil is exploited by the fibrous root system of sugarbeet to a depth of 60 cm within c. 70 days of sowing, and deeper within the following few weeks.…”
Section: Relationships Between N Mtn N Mineralized and N Fertilizersupporting
confidence: 90%
“…In calculating these corrected and adjusted yields of clean beet (CACB) the clean beet was valued at the 1992 'C contracted tonnage' price of £14.48/tonne (Allison & Hetschkun 1995), and the N fertilizer at £0.29/kg. The CACB yields (y) were related to rates of applied N (.v) using the exponential plus linear model as used by George (1984) and Neeteson & Zwetsloot (1989):…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…N in seed meal likely led to more vegetative growth and less tuber development. Adequate management of N is critical for optimal potato yield (Sincik et al 2008), whereas excessive available N results in reduced yields (Lauer 1986;Neeteson and Zwetsloot 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Several variables can impact fertilization at optimum tuber yield: soil type and quality [8,9], organic fertilizers [10,11], preceding crops [12][13][14][15][16], weather conditions [17], irrigation [18], timing, location and chemical form of the fertilizer applied [19], pests and diseases [20] and genetic factors such as cultivar longevity and growth rate [21,22]. Air temperature, photoperiod, day length, intercepted radiation, water abundance, precipitations, root development and crop management were reported to be the driving variables for potato growth and development [8,9,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%